(untitled) (Computer systems and information technologies, 2022)
The results of our research over the past ten years in the field of search engine optimization on the Internet indicate the creation of a new information technology - virtual promotion. The main goal of virtual promotion is to increase the level of sales of goods or services due to technologies that exist in cyberspace. His main idea is to form a so-called market map. This is a new online sales scheme based on the customer’s travel map in cyberspace. This scheme is based on the principle that you earn when you attract a new customer. Then the costs are paid by attracting new customers. That is, the more customers your web content attracts, the more you earn. Therefore, to generate income you need to use WEB services to attract potential customers. Existing product promotion techniques are constantly being improved or new ones are emerging. Therefore, the purpose of the new technology is the formation of new designs from WEB services that ensure maximum efficiency of the process of attracting new customers and retaining existing ones. At the same time it is necessary to consider classical structures of formation of marketing sales channels. We will assume that virtual promotion is an information environment where there are two channels. The first channel has the function of distributing knowledge about the product. The second is product marketing. The first channel forms the technology of information transfer (knowledge) about the product in cyberspace. It concentrates actions on transportation, storage and retrieval of information about a product or service depending on the needs of a potential buyer. Another channel is a network of websites, channel telegrams, marketplaces and video blogs. In other words, the marketing channel is formed by real firms that buy and sell information or knowledge about goods or services in cyberspace. Thus, the task is to form a map of virtual promotion, which describes the structure of the marketing channel of the product through the virtual space.